Expressão gênica de enzimas produzidas no rúmen de ovinos de diferentes classes sexuais submetidos a restrição alimentar - Evangelista, Monalisa Eva Santos (2022)
Considered important genetic and socioeconomic resources, sheep are widely used in agriculture in tropical regions. The integration of techniques from the most diverse areas of research brings more resources for characterization and maintenance of these species, in particular, about the functionality of the ruminal environment through the gene expression of microbial enzymes that act in the transformation of plant biomass. The aim of this study was to evaluate the influence of feed restriction (ad libitum, 30 and 60% restriction) and sexual classes (whole males, castrated males and females) on the gene expression of enzymes produced by ruminal microorganisms in sheep Morada Nova and validate an RNA extraction protocol for recently slaughtered sheep. Twenty-seven lambs of approximately 240 days of age were used, which were managed for 120 days in individual stalls, receiving a diet formulated in a ratio of roughage and concentrate 60:40, based on Tifton-85 grass hay (Cynodon sp.), ground corn and soybean meal. The experiment was carried out in a completely randomized design in 3x3 factorial scheme, totaling 9 treatments. The rumen content was collected after slaughter the animals and destined to determine the gene expression of enzymes produced by bacteria and archaea through qPCR amplifications. The adapted protocol of total RNA extraction proved to be efficient and provided good concentrations of genetic material. Target genes: β-D-xylosidase/α-L-arabinofuranosidase (XylB), xylanase (Xyn10D-fae1A), amylase (Amy), methyl coenzyme M reductase α subunit (mcrA) and constitutive genes: 27F/1492R and 342F/806R were amplified satisfactorily. Feed restriction caused a reduction in the gene expression of genes that encode enzymes with fibrolytic activity, XylB and Xyn10D-fae1A (P<0.05). The expression of the Amy gene also showed a slight reduction as a function of dietary levels. On the other hand, a subtle increase in mcrA gene expression was observed, indicating greater methanogenic activity in the rumen environment. It is concluded the obtaining and validation of a protocol to be used in the extraction of total RNA in samples of small ruminant animals, recently slaughtered. Quantitative feed restriction promotes is reduced in the gene expression of enzymes produced in the rumen, especially in enzymes with hemicellulolytic activity, in addition, this possible management strategy does not constitute a good option for reducing methanogenic activity.